An intelligent network algorithm for enhanced security in a mobile ad hoc network. (2017) - Roopa, M.; Raja, S. Selvakumar
A mobile ad hoc network (MANET) is a distributed system with randomly moving nodes. The dynamic changing topology of MANET makes it more vulnerable to different security attacks. An intrusion detection system (IDS) is used to provide a security layer to protect the networks from various attacks. In this paper, we present the impact of neural-based IDS in detecting a black hole and identify the multi layer perceptron (MLP) as an effective network for providing higher security and accuracy.